Studying rare events in policing: the allure and limitations of using body-worn camera video - Schafer, Joseph (Journal of crime and justice, 2024)
Many intriguing and socially significant policing research questions center on relatively rare events. Scholars may find few viable options to studying those rare events, limiting the development of research to support scientific knowledge and policy responses. The proliferation of body-worn cameras (BWCs) has produced a unique research opportunity through the creation of video archives documenting how officers interact with citizens and police communities. Researchers have access to aspects of police work and behavior previously available only through resource- and time-intensive methodologies, such as field observation. The allure of using video footage is understandably strong, but the limitations of this research methodology need to be understood and ameliorated. This article examines the use of video to support research, focusing on the methodological implications of this emerging research approach. We offer a case study examining police use of force in an east coast department to illustrate the potential and limitations of analyzing video content.